Various Saccharides Addition of Extender Ram Efficiency to Improve Cryopreservation in Semen Etawah Crossbreed Bucks with Seminal Plasma Replacement - nurlatifah, aeni; Sitaresmi, Pradita Iustitia; Hafid, Anita; Mahari, Desiana Ade; Lupitasari, Florentina Bety Indah; Anwar, Rahma Isartina; Santoso, Santoso; Rizal, Muhammad; Herdis, Herdis (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
Phospholipase in buck seminal plasma will trigger a coagulation incident resulting in the demise of the spermatozoa during liquid semen processing using milk or egg yolk substrates diluent. A plasma replacement process is performed to avoid this possibility. The cryopreservation process leads to sperm cell damage due to the freezing process, therefore cryoprotectant agents such as saccharides are required as protective agents. This study aimed to investigate the effect of various types of saccharides on the quality of frozen semen of etawah crossbreed (PE) bucks during cryopreservation and thawing with plasma replacement using Priangan ram semen plasma. Semen was collected using an artificial vagina once a week. Fresh PE bucks semen centrifuged at 3,000 RPM for 30 min. The supernatant (seminal plasma) was removed and replaced in equal volume with Priangan ram seminal plasma. Semen was divided into four treatments: goat semen with sheep semen plasma in Tris diluent (control); control with 0.6% dextrose added (monosaccharides); control with 0.6% sucrose added (disaccharides); control with 0.6% raffinose added (trisaccharides). Semen quality including percentages of motile spermatozoa, live spermatozoa, and intact plasma membrane (IPM) were evaluated after diluted, equilibrated, and thawing, respectively. Results of this study showed that viability and IPM of monosaccharides, disaccharides, and trisaccharides were significantly (P<0.05) higher than control (54.40 and 51.40; 55.00 and 53.60; 55.60 and 52.20 vs 48.40 and 52.20, respectively). The motility of disaccharides was significantly (P<0.05) higher compared to control and other diluent (47.00 vs 41.00, respectively). In conclusion, different types of saccharides were effective in maintaining the quality of etawah crossbreed buck frozen semen. The addition of disaccharides seems more effective compared to monosaccharides and trisaccharides in tris extender on the quality of etawah crossbreed buck frozen semen.